Hybrid Ti02 in Photocatalytic Seawater Desalination : Effect of Operating Time - Ruzinah, Isha; Nurul Hariyah, Abd Majid (2014)
Titanium dioxide (Ti02) is excellently used in various applications including wastewater treatment. It is known to have superb pigmentary properties, high adsorption in the ultraviolet (UV) region, and high stability. The objective of this paper is to study the effect of contact time of seawater desalination in the photocatalytic reaction. The hybrid Ti0 2 catalysts, a mixture of Ti02 and biomass ash, was synthesized via wet impregnation and calcined at 800°C. The photocatalyst was then characterized by using Scanning Electron Microscopy (SEM) and Braunauer-Emmett-Teller (BET). The investigation was carried out in a photoreactor equipped with UV light operated for up to 6 hours with catalyst to seawater weight ratio of 1:400 and stirring speed of 600 rpm. The salt concentration, turbidity and pH of the water were determined prior and after the investigation. The result indicates that the salt concentration gradually decreased as the contact time increased. However, there is no significant change on pH value of the water. It can be concluded that the hybrid Ti02 is able to reduce the seawater salinity effectively.